Trade and Production Fragmentation : Central European Economies in European Union Networks of Production and Marketing - Kaminski, Bartlomiej (World Bank, Washington, DC, 2014)
Developments driven by trade liberalization and tehcnological progress mean that old development strategies, based on state intervention and trade protection, no longer work. Global competition has brought a growing emphasis on product standards, rapid innovation, adaptability, and speedy response. Technology has made possible the fragmentation of production. Firms that become part of global production and distribution networks do not have to be foreign-owned, as many multinationals contract out the delivery of services and products. Foreign involvement facilitates the transfer of managerial and technological know-how, so firms benefit from becoming part of a network. Small producers, rather than servicing small local markets, can supply large firms abroad. Foreign participation--through outsourcing or direct investments--may offer direct access to a parent company's global networks. Becoming part of a multinational's production and distribution network is a cheap way to market products. But the unprecedented globalization of the production process has brought the integration of trade and the disintegration of production, with deep implications for the international division of labor. Have Central European economies been able to take advantage of the global fragmentation and disintegration of production and the division of labor? Ten countries--Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia, and Slovenia--have made large strides toward readjusting their production structures to international markets, mainly in the European Union. And trade in industrial products has lost its pre-transition idiosyncratic character. All 10 economies apear to be on the same track as the European Union in changing patterns of trade with the networks the authors discuss. Progress is advanced in furniture (most of the 10 economies) and automobiles (the Czech Republic, Hungary, Poland, Slovakia, and Slovenia) and is gaining momentum in "information revolution" networks (Estonia and Hungary). Progress in industrial integration with the European Union has been uneven. The first-tier economies (the Czech Republic, Estonia, Hungary, Poland, Slovakia, and Slovenia) are much less so and, despite relatively low wages, have no comparative advantage in assembly in EU markets. Among first-tier economies, three stand out: Estonia and Hungary (in integration into "information revolution" markets) and Slovakia (in restructuring its automotive sector).